Understanding the Bugkalot Cultural Heritage Among Secondary School Teachers in a Philippine DepEd District: Towards Developing Educational Materials on Cultural Heritage - Narciso R. Cardenas; Darwin Don M. Dacles (Research and Advances in Education, 2024)
Cultural heritage shapes communities and identities, fostering pride and a sense of responsibility for its preservation. This study employed a quantitative design using a descriptive-comparative method and a survey. It primarily assessed teachers’ knowledge of cultural heritage in general, as well as their understanding of the Bugkalot people and their tangible and intangible cultural heritage. The findings show a predominance of female educators and a mix of teaching experiences, highlighting the need for culturally relevant resources that cater to both new and experienced teachers, especially Bugkalot educators. Additionally, respondents exhibited moderate knowledge of cultural heritage, with gaps in understanding cultural laws, pointing to a need for targeted professional development focused on Bugkalot traditions and legal frameworks. Sex, teaching experience, ethnicity, and the type of learning materials used did not significantly affect cultural knowledge, emphasizing the need for universal efforts to improve understanding of intangible heritage across all groups. Ultimately, the study reveals that while secondary school teachers in Nagtipunan, Quirino, possess moderate knowledge of Bugkalot cultural heritage — both tangible and intangible — significant gaps remain in their understanding of deeper cultural practices, legal rights, and preservation efforts. This underscores the need for specialized educational resources and professional development to empower educators and strengthen cultural revitalization efforts within the community. A brochure based on the study’s findings has been created. It is recommended that authorities review it for distribution to the relevant groups and individuals.